EVALUATING THE IMPLEMENTATION OF SUBJECT AREA SCIENCE CLUB PROGRAM USING CIPP MODEL - Jupri Marsal; Yusuf Avicena; Siti Fermaisuri (RADJA PUBLIKA, 2025)
This study evaluates the implementation of the Science Club program in the field of study at MAN Insan Cendekia, Batam City using the CIPP (Context, Input, Process, Product) model. This club aims to develop students' interests, talents, and competencies in science and support the strengthening of the profile of superior science students. Data were obtained through a mixed method: questionnaire (Likert scale), interviews, observations, and documentation. The results indicated that the program was quite effective with all aspects rated as